Peningkatan Interaktif Belajar melalui Program Rabu Gembira Bagi Siswa Kelas 1-6 SD di Kampung Rama - Salomo Rudianto (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The Rabu Gembira program at GKSI Kampung Rama is an initiative designed to support the character development and spirituality of children through a series of creative and educational activities. With a comprehensive approach, this program not only teaches Christian values but also equips children with life skills and a high level of social awareness. Activities including crafts, spiritual discussions, and social interactions aim to shape individuals who are character-driven and capable of making a positive impact in their communities. Through this experience, children learn to embody values of truth, enhance their self-confidence, and develop social and emotional skills. The outcomes of this program are expected to prepare the younger generation to face the challenges of the times with confidence and strong personal qualities. This discussion provides an in-depth understanding of the goals, benefits, and positive impacts of the Rabu Gembira program in supporting the holistic development of children.